RADI-25. REPEAT STEREOTACTIC RADIOSURGERY FOR RECURRENT BRAIN METASTASES. (12th August 2019) - Krivosheya, Daria; Borghei-Razavi, Hamid; Grabowski, Matthew; Angelov, Lilyana; Barnett, Gene; Vogelbaum, Michael; Chao, Samuel; Murphy, Erin; Yu, Jennifer; Ahluwalia, Manmeet; Suh, John; Mohammadi, Alireza
Abstract: INTRODUCTION: Mainstream modality of treatment of oligo-metastatic disease is stereotactic radiosurgery (SRS). While the local control rate is nearing 90%, 7% of lesions and 10 to 15% of patients develop radiation necrosis post treatment. In the face of increasing lesion size and evidence of recurrence, re-treatment of the enlarging lesion with radiosurgery can be attempted. The aim of the project is to evaluate outcomes of lesions treated with repeat SRS. METHODS: We conducted a retrospective review of all patients that were treated with Gamma Knife radiosurgery at our institution from 2000 to 2018. Fifty-one lesions in 39 patients were identified that had recurrence during follow-up period and were treated with a second single-fraction SRS. RESULTS: A combination of imaging studies, such as PET and/or perfusion studies, lesion biopsy, and clinical course were used to make the diagnosis of lesion recurrence. The average radiation dose at first treatment was 21 Gy, and the average dose at second treatment was 19 Gy. The median time between treatments was 16.8 months, ranging from 2.5 to 75.3 months, and the median follow-up after second treatment was 10.2 months. Of 51 lesions that received two SRS treatments, 49% (25 lesions) continued to progress at a median interval of 4.8 months post treatment, of which 35% (18 lesions) were diagnosed as radiation necrosis based on biopsy results or advanced brain imaging. The overall rate of radiation necrosis post second SRS treatment was determined to be 16% per lesion and 21% per patient. CONCLUSION: Recurrent brain metastases that are re-treated with single fraction SRS are associated with a higher risk of radiation necrosis. Alternative treatment strategies, including fractionation of subsequent SRS treatments, radiation dose reduction, and combination with laser ablation could be considered to ensure symptom and disease control to reduce the rate of subsequent radiation necrosis.